Conductive material with good wear resistance for electromagnetic shielding window and preparation method of conductive material

By using resin base material, antioxidant metal material and carbon-based filler combinations in electromagnetic shielding window materials, the problem of insufficient oxidation and mechanical properties of conductive materials is solved, and higher conductivity and durability are achieved, ensuring that Effective use of electromagnetic shielded windows.

CN119264748APending Publication Date: 2025-01-07HEFEI ZHONGYIN NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411825012.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing conductive materials used in electromagnetic shielding windows are not highly oxidation resistance and aging resistance, which easily forms oxide layers, reduces conductivity, and have poor mechanical properties, lack good adhesion and wear resistance, which affects shielding performance and Service life.

Method used

Use resin base material as the skeleton material, combine antioxidant metal materials and carbon-based fillers, and add auxiliary additives such as nanosilicon dioxide to prepare conductive materials through specific preparation methods, including the preparation and pretreatment of silver-plated copper powder, and mix differently The types of resins, metal powders and carbon-based fillers are used to form conductive coating materials such as organic leveling agents, anti-deposition agents and coupling agents.

Benefits of technology

It improves the oxidation resistance, aging resistance and conductivity of conductive materials, enhances adhesion and wear resistance, extends service life, and ensures the normal use and efficient shielding performance of electromagnetic shielding windows.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264748A_ABST
    Figure CN119264748A_ABST
Patent Text Reader

Abstract

The invention discloses a conductive material with good wear resistance for an electromagnetic shielding window and a preparation method thereof, and relates to the technical field of conductive materials, the conductive material comprises a resin base material, an antioxidant metal material, a carbon filler, nano-silica, a leveling agent, an anti-settling agent, a dispersant, a coupling agent and a solvent; according to the conductive material for the electromagnetic shielding window, the resin base material is used as a framework material of the conductive material, the antioxidant metal material and the carbon filler are used as conductive filler of the conductive material, and auxiliary additives such as the nano silicon dioxide are added to prepare the conductive material for the electromagnetic shielding window; the prepared conductive material has good oxidation resistance and aging resistance, an oxide layer is not easy to form after long-time use, so that the conductivity and the shielding performance are improved to a certain extent, in addition, the conductive material also has good adhesive force and wear resistance, the durability of the conductive material is further improved, and the service life of the conductive material is prolonged. And normal use of the electromagnetic shielding window can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive materials, and in particular to a conductive material for an electromagnetic shielding window with good wear resistance and a preparation method thereof. Background Art

[0002] Electromagnetic shielding windows are usually used to block electromagnetic radiation. They can effectively prevent the penetration of electromagnetic waves to protect equipment or personnel from electromagnetic interference or electromagnetic radiation. These windows can be used in various applications, including in laboratories, medical facilities, aerospace, electronic equipment and other fields. They are usually made of special materials with the ability to shield electromagnetic waves, such as metallized plastics, metal grid glass, etc. The design should take into account the range and intensity of electromagnetic wave frequencies to ensure effective shielding of the required electromagnetic radiation.

[0003] During the manufacturing process, electromagnetic shielding windows generally need to be coated with conductive materials to improve their shielding effectiveness against electromagnetic waves. These conductive coating materials usually have good conductivity and can effectively reflect and absorb electromagnetic waves, thereby reducing the impact of electromagnetic radiation on the indoor environment. When selecting conductive coating materials for electromagnetic shielding windows, it is necessary to comprehensively consider factors such as the material's conductivity, light transmittance, weather resistance, cost and processing technology to ensure that the windows can effectively shield electromagnetic waves while meeting aesthetic and usage requirements.

[0004] Most of the existing conductive coating materials for electromagnetic shielding windows are made of a single material, and the prepared conductive coating materials have low antioxidant and aging resistance. After long-term use, an oxide layer is easily formed, thereby reducing the conductivity and causing a negative impact on its shielding performance. In addition, the mechanical properties of the existing conductive coating materials for electromagnetic shielding windows are not high, and they do not have good adhesion and wear resistance. The durability needs to be improved, which affects the normal use of the electromagnetic shielding windows and is not convenient for widespread promotion and application. Therefore, the present invention proposes a conductive material for electromagnetic shielding windows with good wear resistance and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to propose a conductive material for electromagnetic shielding windows with good wear resistance and a preparation method thereof, so as to solve the problems that the existing conductive materials for electromagnetic shielding windows have low antioxidant properties and aging resistance, and are prone to form an oxide layer after long-term use, thereby reducing the conductivity and causing a negative impact on its shielding performance, as well as low mechanical properties, lack of good adhesion and wear resistance, and durability needs to be improved.

[0006] In order to achieve the purpose of the present invention, the present invention is implemented through the following technical scheme: a conductive material for electromagnetic shielding windows with good wear resistance, comprising the following raw materials in parts by weight: 150 to 200 parts of resin base material, 100 to 150 parts of antioxidant metal material, 20 to 30 parts of carbon filler, 2 to 3 parts of nano-silicon dioxide, 10 to 20 parts of leveling agent, 1 to 3 parts of anti-settling agent, 1 to 3 parts of dispersant, 2 to 3 parts of coupling agent and 50 to 80 parts of solvent.

[0007] A further improvement is that the resin base material is prepared by mixing acrylic resin, polyurethane resin and alkyd resin, and the mixing mass ratio of the acrylic resin, polyurethane resin and alkyd resin is 3-5:2-3:1.

[0008] The further improvement is that: the antioxidant metal material is silver-plated copper powder, and the preparation method of the silver-plated copper powder is: firstly, copper powder and silver nitrate are weighed in a mass ratio of 100:3-4 for standby use, then the weighed silver nitrate is dissolved in water to form a silver ion solution, then a reducing agent and a stabilizer are added to the silver ion solution, and the pH value of the solution is adjusted to 9-11 to obtain a silver ion plating solution, and then the weighed copper powder is added to the silver ion plating solution for chemical plating reaction, so that the silver ions in the silver ion plating solution are reduced to silver atoms on the surface of the copper powder until a silver layer is deposited, and then the silver-plated copper powder is washed clean with deionized water, and finally dried to obtain the silver-plated copper powder.

[0009] A further improvement is that the copper powder is pretreated before silver plating. The specific steps are: first, the copper powder is cleaned with deionized water to remove dirt on the surface of the copper powder, and then the copper powder is cleaned for a second time with a hydrochloric acid solution to remove the oxide layer on the surface of the copper powder and activate the surface of the copper powder. After cleaning, the copper powder is dried to complete the pretreatment.

[0010] A further improvement is that the mass ratio of the silver nitrate, water, reducing agent and stabilizer is 3:100:1:1, the reducing agent is selected from one of glucose or hydrazine, and the stabilizer is selected from one of sodium thiosulfate or sodium thiocyanate.

[0011] A further improvement is that the carbon-based filler is prepared by mixing graphite powder, carbon black powder and graphene powder, and the mixing mass ratio of the graphite powder, carbon black powder and graphene powder is 5:2:1.

[0012] A further improvement is that the leveling agent is selected from one of an organic silicon leveling agent or a polyurethane leveling agent, the anti-settling agent is organic bentonite, the dispersant is an organic siloxane dispersant, the coupling agent is selected from one of a titanate coupling agent or an aluminate coupling agent, and the solvent is selected from one of an acetone solvent or a methyl ethyl ketone solvent.

[0013] A method for preparing a conductive material for an electromagnetic shielding window with good wear resistance comprises the following steps: Step 1: first use a weighing instrument to weigh 150-200 parts of a resin base material, 100-150 parts of an antioxidant metal material, 20-30 parts of a carbon filler, 2-3 parts of nano-silicon dioxide, 10-20 parts of a leveling agent, 1-3 parts of an anti-settling agent, 1-3 parts of a dispersant, 2-3 parts of a coupling agent and 50-80 parts of a solvent according to the following weight parts, and set them aside; Step 2: Then, the antioxidant metal material is added to the resin base material and mixed and stirred evenly by a high-speed mixer, and then the carbon filler and nano-silicon dioxide are added to the high-speed mixer and continued to mix and stir, and the conductive paste is obtained after stirring evenly; Step 3: Then, add the leveling agent, anti-settling agent, dispersant and coupling agent to the conductive slurry in turn and keep stirring at a constant speed. After stirring evenly, add the solvent and continue mixing and stirring. Finally, filter through a filter to remove impurities and large particles that are not fully dispersed, and obtain a conductive coating material for electromagnetic shielding windows.

[0014] The beneficial effects of the present invention are as follows: the present invention adopts a resin base material as the skeleton material of the conductive material, and adopts antioxidant metal materials and carbon-based fillers as conductive fillers of the conductive material, and simultaneously adds auxiliary additives such as nano-silicon dioxide to make a conductive material for electromagnetic shielding windows, so that the prepared conductive material has good antioxidant and aging resistance, and is not easy to form an oxide layer after long-term use, thereby improving the conductivity and shielding performance to a certain extent. In addition, it also has good adhesion and wear resistance, further improving the durability of the conductive material, thereby ensuring the normal use of the electromagnetic shielding window, and is worthy of wide promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 It is a schematic diagram of the preparation process of the conductive material for the electromagnetic shielding window of the present invention. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Embodiment 1 This embodiment provides a conductive material for electromagnetic shielding windows with good wear resistance, comprising the following raw materials in parts by weight: 150 parts of a resin base material, 100 parts of an antioxidant metal material, 20 parts of a carbon filler, 2 parts of nano-silicon dioxide, 10 parts of a leveling agent, 1 part of an anti-settling agent, 1 part of a dispersant, 2 parts of a coupling agent, and 50 parts of a solvent; In this embodiment, the resin base material is prepared by mixing acrylic resin, polyurethane resin and alkyd resin in a mass ratio of 3:2:1. The resin base material composed of acrylic resin, polyurethane resin and alkyd resin as the skeleton material of the coating can effectively improve the adhesion ability of the subsequent conductive coating material; In this embodiment, the antioxidant metal material is silver-plated copper powder. The preparation method of the silver-plated copper powder is: first weigh copper powder and silver nitrate in a mass ratio of 100:3 for use, then dissolve the weighed silver nitrate in water to form a silver ion solution, then add a reducing agent and a stabilizer to the silver ion solution, and adjust the pH value of the solution to 9 to obtain a silver ion plating solution, wherein the mass ratio of silver nitrate, water, reducing agent and stabilizer is 3:100:1:1, the reducing agent is glucose, and the stabilizer is sodium thiosulfate, then add the weighed copper powder to the silver ion plating solution for chemical plating reaction, so that the silver ions in the silver ion plating solution are reduced to silver atoms on the surface of the copper powder until a silver layer is deposited, and then the silver-plated copper powder is washed clean with deionized water, and finally dried to obtain the silver-plated copper powder. The copper powder is pretreated before silver plating. The specific steps are: first, the copper powder is washed with deionized water to remove dirt on the surface of the copper powder, and then the copper powder is washed twice with hydrochloric acid solution (12mol / L) to remove the oxide layer on the surface of the copper powder and activate the surface of the copper powder. After washing, it is dried to complete the pretreatment. The copper powder is silver-plated to make an antioxidant metal material as a conductive filler for the coating, which can effectively improve the antioxidant performance, anti-aging performance and conductive performance of the subsequent conductive coating material, and improve the shielding effect; In this embodiment, the carbon-based filler is prepared by mixing graphite powder, carbon black powder and graphene powder in a mass ratio of 5:2:1. The carbon-based filler is prepared by mixing graphite powder, carbon black powder and graphene powder to serve as a secondary conductive filler for the coating, which can effectively improve the wear resistance and durability of the subsequent conductive coating material.

[0019] In this embodiment, the leveling agent is an organic silicone leveling agent, which is used to improve the fluidity and leveling of the coating. The anti-settling agent is an organic bentonite, which is used to ensure the stability of the coating. The dispersant is an organic siloxane dispersant, which is used to prevent aggregation and sedimentation in the coating. The coupling agent is a titanate coupling agent, and the solvent is an acetone solvent, which is used to adjust the viscosity of the coating. By adding the above auxiliary additives, the comprehensive performance of the subsequent conductive coating material can be further improved.

[0020] See also Figure 1 This embodiment also provides a method for preparing a conductive material for an electromagnetic shielding window with good wear resistance, comprising the following steps: Step 1: first use a weighing instrument to weigh 150 parts of a resin base material, 100 parts of an antioxidant metal material, 20 parts of a carbon filler, 2 parts of nano-silicon dioxide, 10 parts of a leveling agent, 1 part of an anti-settling agent, 1 part of a dispersant, 2 parts of a coupling agent and 50 parts of a solvent according to the following weight parts, and set them aside; Step 2: Then, the antioxidant metal material is added to the resin base material and mixed and stirred evenly by a high-speed mixer, and then the carbon filler and nano-silicon dioxide are added to the high-speed mixer and continued to mix and stir, and the conductive paste is obtained after stirring evenly; Step 3: Then, add the leveling agent, anti-settling agent, dispersant and coupling agent to the conductive slurry in turn and keep stirring at a constant speed. After stirring evenly, add the solvent and continue mixing and stirring. Finally, filter through a filter to remove impurities and large particles that are not fully dispersed, and obtain a conductive coating material for electromagnetic shielding windows.

[0021] Embodiment 2 This embodiment provides a conductive material for electromagnetic shielding windows with good wear resistance, including the following raw materials in parts by weight: 175 parts of resin base material, 125 parts of antioxidant metal material, 25 parts of carbon filler, 2 parts of nano silicon dioxide, 15 parts of leveling agent, 2 parts of anti-settling agent, 2 parts of dispersant, 2 parts of coupling agent and 65 parts of solvent; In this embodiment, the resin base material is prepared by mixing acrylic resin, polyurethane resin and alkyd resin in a mass ratio of 4:2:1. The resin base material composed of acrylic resin, polyurethane resin and alkyd resin as the skeleton material of the coating can effectively improve the adhesion ability of the subsequent conductive coating material; In this embodiment, the antioxidant metal material is silver-plated copper powder. The preparation method of the silver-plated copper powder is: first weigh copper powder and silver nitrate in a mass ratio of 100:3 for use, then dissolve the weighed silver nitrate in water to form a silver ion solution, then add a reducing agent and a stabilizer to the silver ion solution, and adjust the pH value of the solution to 10 to obtain a silver ion plating solution, wherein the mass ratio of silver nitrate, water, reducing agent and stabilizer is 3:100:1:1, the reducing agent is glucose, and the stabilizer is sodium thiosulfate, then add the weighed copper powder to the silver ion plating solution for chemical plating reaction, so that the silver ions in the silver ion plating solution are reduced to silver atoms on the surface of the copper powder until a silver layer is deposited, and then the silver-plated copper powder is washed clean with deionized water, and finally dried to obtain the silver-plated copper powder. The copper powder is pretreated before silver plating. The specific steps are: first, the copper powder is washed with deionized water to remove dirt on the surface of the copper powder, and then the copper powder is washed twice with hydrochloric acid solution (12mol / L) to remove the oxide layer on the surface of the copper powder and activate the surface of the copper powder. After washing, it is dried to complete the pretreatment. The copper powder is silver-plated to make an antioxidant metal material as a conductive filler for the coating, which can effectively improve the antioxidant performance, anti-aging performance and conductive performance of the subsequent conductive coating material, and improve the shielding effect; In this embodiment, the carbon-based filler is prepared by mixing graphite powder, carbon black powder and graphene powder in a mass ratio of 5:2:1. The carbon-based filler is prepared by mixing graphite powder, carbon black powder and graphene powder to serve as a secondary conductive filler for the coating, which can effectively improve the wear resistance and durability of the subsequent conductive coating material.

[0022] In this embodiment, the leveling agent is an organic silicone leveling agent, which is used to improve the fluidity and leveling of the coating. The anti-settling agent is an organic bentonite, which is used to ensure the stability of the coating. The dispersant is an organic siloxane dispersant, which is used to prevent aggregation and sedimentation in the coating. The coupling agent is a titanate coupling agent, and the solvent is an acetone solvent, which is used to adjust the viscosity of the coating. By adding the above auxiliary additives, the comprehensive performance of the subsequent conductive coating material can be further improved.

[0023] See also Figure 1 This embodiment also provides a method for preparing a conductive material for an electromagnetic shielding window with good wear resistance, comprising the following steps: Step 1: first, using a weighing instrument, weigh 175 parts of a resin base material, 125 parts of an antioxidant metal material, 25 parts of a carbon-based filler, 2 parts of nano-silicon dioxide, 15 parts of a leveling agent, 2 parts of an anti-settling agent, 2 parts of a dispersant, 2 parts of a coupling agent, and 75 parts of a solvent according to the following weight parts, and set aside; Step 2: Then, the antioxidant metal material is added to the resin base material and mixed and stirred evenly by a high-speed mixer, and then the carbon filler and nano-silicon dioxide are added to the high-speed mixer and continued to mix and stir, and the conductive paste is obtained after stirring evenly; Step 3: Then, add the leveling agent, anti-settling agent, dispersant and coupling agent to the conductive slurry in turn and keep stirring at a constant speed. After stirring evenly, add the solvent and continue mixing and stirring. Finally, filter through a filter to remove impurities and large particles that are not fully dispersed, and obtain a conductive coating material for electromagnetic shielding windows.

[0024] Embodiment 3 This embodiment provides a conductive material for electromagnetic shielding windows with good wear resistance, comprising the following raw materials in parts by weight: 200 parts of a resin base material, 150 parts of an antioxidant metal material, 30 parts of a carbon filler, 3 parts of nano-silicon dioxide, 20 parts of a leveling agent, 3 parts of an anti-settling agent, 3 parts of a dispersant, 3 parts of a coupling agent, and 80 parts of a solvent; In this embodiment, the resin base material is prepared by mixing acrylic resin, polyurethane resin and alkyd resin in a mass ratio of 5:3:1. The resin base material composed of acrylic resin, polyurethane resin and alkyd resin as the skeleton material of the coating can effectively improve the adhesion ability of the subsequent conductive coating material; In this embodiment, the antioxidant metal material is silver-plated copper powder. The preparation method of the silver-plated copper powder is as follows: first, copper powder and silver nitrate are weighed in a mass ratio of 100:4 for standby use, and then the weighed silver nitrate is dissolved in water to form a silver ion solution, and then a reducing agent and a stabilizer are added to the silver ion solution, and the pH value of the solution is adjusted to 11 to obtain a silver ion plating solution, wherein the mass ratio of silver nitrate, water, reducing agent and stabilizer is 3:100:1:1, the reducing agent is hydrazine, and the stabilizer is sodium thiocyanate, and then the weighed copper powder is added to the silver ion plating solution for chemical plating reaction, so that the silver ions in the silver ion plating solution are reduced to silver atoms on the surface of the copper powder until a silver layer is deposited, and then the silver-plated copper powder is washed clean with deionized water, and finally dried to obtain the silver-plated copper powder. The copper powder is pretreated before silver plating. The specific steps are: first, the copper powder is washed with deionized water to remove dirt on the surface of the copper powder, and then the copper powder is washed twice with hydrochloric acid solution (12mol / L) to remove the oxide layer on the surface of the copper powder and activate the surface of the copper powder. After washing, it is dried to complete the pretreatment. The copper powder is silver-plated to make an antioxidant metal material as a conductive filler for the coating, which can effectively improve the antioxidant performance, anti-aging performance and conductive performance of the subsequent conductive coating material, and improve the shielding effect; In this embodiment, the carbon-based filler is prepared by mixing graphite powder, carbon black powder and graphene powder in a mass ratio of 5:2:1. The carbon-based filler is prepared by mixing graphite powder, carbon black powder and graphene powder to serve as a secondary conductive filler for the coating, which can effectively improve the wear resistance and durability of the subsequent conductive coating material.

[0025] In this embodiment, the leveling agent is a polyurethane leveling agent, which is used to improve the fluidity and leveling of the coating. The anti-settling agent is an organic bentonite, which is used to ensure the stability of the coating. The dispersant is an organic silicone dispersant, which is used to prevent aggregation and sedimentation in the coating. The coupling agent is an aluminate coupling agent, and the solvent is a methyl ethyl ketone solvent, which is used to adjust the viscosity of the coating. By adding the above-mentioned auxiliary additives, the comprehensive performance of the subsequent conductive coating material can be further improved.

[0026] See also Figure 1 This embodiment also provides a method for preparing a conductive material for an electromagnetic shielding window with good wear resistance, comprising the following steps: Step 1: first use a weighing instrument to weigh 200 parts of a resin base material, 150 parts of an antioxidant metal material, 30 parts of a carbon filler, 3 parts of nano-silicon dioxide, 20 parts of a leveling agent, 3 parts of an anti-settling agent, 3 parts of a dispersant, 3 parts of a coupling agent and 80 parts of a solvent according to the following weight parts, and set them aside; Step 2: Then, the antioxidant metal material is added to the resin base material and mixed and stirred evenly by a high-speed mixer, and then the carbon filler and nano-silicon dioxide are added to the high-speed mixer and continued to mix and stir, and the conductive paste is obtained after stirring evenly; Step 3: Then, add the leveling agent, anti-settling agent, dispersant and coupling agent to the conductive slurry in turn and keep stirring at a constant speed. After stirring evenly, add the solvent and continue mixing and stirring. Finally, filter through a filter to remove impurities and large particles that are not fully dispersed, and obtain a conductive coating material for electromagnetic shielding windows.

[0027] The conductive materials for electromagnetic shielding windows prepared in Example 1, Example 2 and Example 3 of the present invention were tested and compared with the Osbon conductive paint (comparison sample) currently available on the market (volume resistivity was tested using the GB / T1692-2008 test method, adhesion was tested using the GB / T5210-2006 test method, and hardness was tested using the GB / T6739-2006 test method). The results are shown in Table 1 below: Table 1 Test results

[0028] It can be seen from Table 1 above that compared with the comparison samples, the conductive materials for electromagnetic shielding windows prepared in Example 1, Example 2 and Example 3 of the present invention have lower volume resistivity after aging at a high temperature of 100°C for 100 hours, that is, high conductivity and good electromagnetic shielding performance. At the same time, it shows that it has good antioxidant ability and aging resistance, and has high adhesion and hardness, indicating that it has good wear resistance.

[0029] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A conductive material for electromagnetic shielding windows with good wear resistance, characterized in that: The invention comprises the following raw materials in parts by weight: 150-200 parts of resin base material, 100-150 parts of antioxidant metal material, 20-30 parts of carbon filler, 2-3 parts of nano silicon dioxide, 10-20 parts of leveling agent, 1-3 parts of anti-settling agent, 1-3 parts of dispersant, 2-3 parts of coupling agent and 50-80 parts of solvent.

2. The conductive material for electromagnetic shielding windows with good wear resistance according to claim 1, characterized in that: The resin base material is prepared by mixing acrylic resin, polyurethane resin and alkyd resin, and the mixing mass ratio of the acrylic resin, polyurethane resin and alkyd resin is 3-5:2-3:

1.

3. The conductive material for electromagnetic shielding windows with good wear resistance according to claim 1, characterized in that: The antioxidant metal material is silver-plated copper powder. The preparation method of the silver-plated copper powder is as follows: firstly, copper powder and silver nitrate are weighed in a mass ratio of 100:3-4 for standby use, then the weighed silver nitrate is dissolved in water to form a silver ion solution, then a reducing agent and a stabilizer are added to the silver ion solution, and the pH value of the solution is adjusted to 9-11 to obtain a silver ion plating solution, then the weighed copper powder is added to the silver ion plating solution for chemical plating reaction, so that the silver ions in the silver ion plating solution are reduced to silver atoms on the surface of the copper powder until a silver layer is deposited, then the silver-plated copper powder is washed clean with deionized water, and finally dried to obtain the silver-plated copper powder.

4. The conductive material for electromagnetic shielding windows with good wear resistance according to claim 3, characterized in that: The copper powder is pretreated before silver plating, and the specific steps are: first, the copper powder is cleaned with deionized water to remove dirt on the surface of the copper powder, and then the copper powder is cleaned twice with a hydrochloric acid solution to remove the oxide layer on the surface of the copper powder and activate the surface of the copper powder. After cleaning, the copper powder is dried to complete the pretreatment.

5. The conductive material for electromagnetic shielding windows with good wear resistance according to claim 3, characterized in that: The mass ratio of the silver nitrate, water, reducing agent and stabilizer is 3:100:1:1, the reducing agent is selected from one of glucose or hydrazine, and the stabilizer is selected from one of sodium thiosulfate or sodium thiocyanate.

6. The conductive material for electromagnetic shielding windows with good wear resistance according to claim 1, characterized in that: The carbon-based filler is prepared by mixing graphite powder, carbon black powder and graphene powder, and the mixing mass ratio of the graphite powder, carbon black powder and graphene powder is 5:2:

1.

7. The conductive material for electromagnetic shielding windows with good wear resistance according to claim 1, characterized in that: The leveling agent is selected from one of an organic silicon leveling agent or a polyurethane leveling agent, the anti-settling agent is organic bentonite, the dispersant is an organic siloxane dispersant, the coupling agent is selected from one of a titanate coupling agent or an aluminate coupling agent, and the solvent is selected from one of an acetone solvent or a methyl ethyl ketone solvent.

8. A method for preparing a conductive material for an electromagnetic shielding window with good wear resistance as claimed in claim 1, characterized in that: The following steps are involved: Step 1: first use a weighing instrument to weigh 150-200 parts of a resin base material, 100-150 parts of an antioxidant metal material, 20-30 parts of a carbon filler, 2-3 parts of nano-silicon dioxide, 10-20 parts of a leveling agent, 1-3 parts of an anti-settling agent, 1-3 parts of a dispersant, 2-3 parts of a coupling agent and 50-80 parts of a solvent according to the following weight parts, and set them aside; Step 2: Then, the antioxidant metal material is added to the resin base material and mixed and stirred evenly by a high-speed mixer, and then the carbon filler and nano-silicon dioxide are added to the high-speed mixer and continued to mix and stir, and the conductive paste is obtained after stirring evenly; Step 3: Then, add the leveling agent, anti-settling agent, dispersant and coupling agent to the conductive slurry in turn and keep stirring at a constant speed. After stirring evenly, add the solvent and continue mixing and stirring. Finally, filter through a filter to remove impurities and large particles that are not fully dispersed, and obtain a conductive coating material for electromagnetic shielding windows.

Citation Information

Patent Citations

  • Method for preparing uniform silver conducting layer on surface of metal or nonmetal material

    CN102002694A

  • Silver-plated copper powder and preparation method thereof

    CN102814496A

  • Copper-based electromagnetic shielding coating and preparation method thereof

    CN104530873A

  • Electromagnetic shielding conductive paint for civil air defense door and preparation method of electromagnetic shielding conductive paint

    CN106752632A

  • Electromagnetic shielding paint used for high- and low-voltage electrical appliances and a preparing method thereof

    CN107286808A